Pemodelan Premi Asuransi Bencana Kematian pada Ternak Sapi dengan Pengaruh Fatal Shock - Natasha Maria; Felivia Kusnadi; Farah Kristiani (Limits: Journal of Mathematics and Its Applications, 2022)
Cattle farming is one of the highest demands of occupation by Indonesians as the source of income. If in a farm there are cattle with an infectious disease, thus it will cause them sick or even die, hence the infected cattle cannot provide maximum benefits. As a result, the farmer's income will decrease or incurred losses. Therefore, cattle insurance become one preventive way to divert the risk of financial losses incurred by cattle breeders. The expectation of losses is determined by the effect of fatal shock, namely the arrival time of the Brucellosis disease which follows a Poisson process. The distribution of loss amounts occurs as a mixture distribution of the binomial and degenerate distribution from a random variables of remaining cattle's future lifetime with influence of fatal shock, which is then modeled by determining the loss distribution incurred by the insurance company as a modification of the insurance policy with deductible, policy limit, and co-insurance. Insurance premium is obtained using the Pure Premium Method which uses the expectation of losses. Based on the calculation that used cattle population data in Bogor Regency, the premium rate increases as the policy limits, rate of Brucellosis disease arrival time, number of cattles insured, and cattle’s age increase. However, the premium rate will decrease if the deductible increases.